Human resource utilization improvements in a pharmaceutical plant - Fan, Siyu (2014)
This study examines issues that impact the human resource utilization in the Active Pharmaceutical Ingredient (API) facility in a pharmaceutical manufacturing plant in Singapore. These issues include the ways of multi-tasking by operators, operators’ leave-taking behaviors, and the loss of production time due to operator slack. Both qualitative inputs from interviews with managers and operators and quantitative analyses of the production data are used to investigate the issues. The results show that the task allocations and definition of responsibilities among operators could be further optimized and a centralization model is proposed to illustrate the possible time-savings. It is also argued that additional information of process time should be provided to the operators to support them in multi-tasking. In addition, to overcome the fluctuations of manpower availability, operators’ leave-taking behaviors over 2007 are investigated and some key insights are highlighted to assist management in designing human resource policies to ensure the smooth running of the plant. Lastly, a performance metric tailored to the specific manufacturing requirements of API is designed. Such a performance metric is tied directly to the operations of key cycle-time limiting vessels and can be integrated into a broader performance evaluation matrix to motivate operators to work towards the common goal of reducing overall process cycle time in API manufacturing.